Paradigma Konstruktivistik dalam Pembelajaran: Telaah Tokoh, Tipologi, dan Pendekatan Pedagogis - Shabira Nur Izzah; Muhammad Tajudin Alwy; M. Yunus Abu Bakar (JOURNAL SAINS STUDENT RESEARCH, 2026)
This study aims to examine constructivist theory in learning, including its main figures, types of theories, and learning approaches relevant to modern education. Constructivist theory emphasizes that knowledge is actively constructed by learners through experience and interaction with their environment. The results of the study indicate that the key figures in constructivism include Jean Piaget, Lev Vygotsky, and Jerome Bruner, each contributing significantly to the development of learning theories. In addition, there are several types of constructivism, namely cognitive constructivism, social constructivism, and radical constructivism, which have different characteristics and emphases. In practice, constructivist learning approaches emphasize student-centered learning, active participation, experiential learning, and social interaction. Therefore, the application of constructivist theory in learning can enhance critical thinking skills, creativity, and learners’ independence, making it highly relevant for implementation at various levels of education in the modern era.